Rancang Bangun Alat Monitoring Nutrisi Kebun Hidroponik - Rouhillah; Inzar Salfikar; Javid Hamar (Politeknik Aceh, 2021)
Hydroponics is a way of farming that does not use soil as a planting medium, but its uses water that contains nutrients. In the growth of hydroponic plants, it can be affected by various factors, one of them is the delay in adding hydroponic water nutrients. This research aims to create a system monitoring nutrient levels and water availability in reservoir. Then, the microcontroller processes the data and sends the data with the help of NodeMcu ESP8266 to Firebase. The data in Firebase will be forwarded to Android using the MIT App Inventor software with Internet of Thing (IoT) technology. In this research, the hydroponic plants used are lettuce which has a nutritional value of around 560 - 840 in units of parts per million (ppm). As a result of testing, the sensor is not able to measure nutrient levels reaching 850 ppm and the xkc-y25 sensor can detect water in a full or reduced reservoir, all of these sensors data are measured in real time, and can be monitored via android.